Performance-based variations in dynamic generation of e-learning web-based presentations - Khor, Ean-Teng; Yeoh, Eng-Thiam (ACTA Press Anaheim, 2006)
The paper describes the general view of MKBe-Learning System architecture and illustrates the design of presentation Generator in MKBe-Learning System. Besides, we explain the sequencing behaviors and navigation scenario that will be performed by presentation generator. We have use Basic Electronics subject as our example and the sequencing and navigation process is based on students' performance levels (Weak, Moderate, Advance). The underlying concepts of our solution will generate an appropriate presentation for different requirements or performance levels that ensures the e-Learning system for the students is flexible and tailoring web content to an individual user. With this architecture, the c-Learning System is able to support different levels of adaptively dynamism.